Multiple structures of laminar fuel-rich spray flames in the counterflow configuration - Ying, Zhaoping; Olguín Astudillo, Hernán Andrés; Gutheil, Eva (Combustion and flame, 2022)
Multiple structures of laminar non-premixed ethanol/air spray flames in the counterflow configuration are presented which exist under fuel-rich conditions and moderate gas strain rates. A mono-disperse liquid fuel spray with carrier gas air is directed against an air stream. Two different spray flame structures are found for identical boundary and initial conditions: one of these flame structures consists of two different chemical reaction zones which reside on either side of the gas stagnation plane. In the second case, the spray-sided flame does not exist and combustion occurs entirely on the gas side of the configuration with largely distinct evaporation and combustion zones. Parametric studies of equivalence ratio between 1.1 and 1.8 and gas strain rates on the spray side of the configuration from 55/s as well as initial droplet size between 10 µm and 50 µm are performed. A regime diagram is presented to display the range of existence of the multiple/single structures as well as the flame extinction. Physical reasons for the existence and breakdown of the multiple structures are explored and discussed. The spray flame structure with a single chemical reaction zone breaks down with increased strain rate when the chemical time scales of OH and fuel vapor are equal at the crossover temperature (Tcross=1104 K) of the reaction rate constants of H + O2 ⇌ OH + O and H + O2 + M → HO2 + M.